THE ROLE OF STUDENTSâ MOTIVATIONAL SELF-REGULATION IN STRUCTURE III - Mukti, Thomas Wahyu Prabowo (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
One of the important factors that influence the language learning, especially learning the basic rule of a language, is motivation. Many studies have tried to find out the correlation between motivation and self-regulation with the students academic performance and they find out that both motivation and learning language are correlated so much. Thus, this paper specifically tried to find out the role of studentsâ motivational self-regulation with the studentsâ learning strategy. This research employed quantitative approach by employing survey method using observation sheet, questionnaire, and interview on some participants. The results of this study showed that the studentsâ motivation was high but they cannot self-regulate themselves.Â DOI: doi.org/10.24071/llt.2017.200205